Elevated procalcitonin in a haematological disorder: case report - Raghunath D.; Shankar Balasubramanian; Dhivahar G.; Dr. Shivanshu Misra (Tropical Journal of Pathology and Microbiology, 2020)
Serum procalcitonin (PCT) is a biochemical marker of sepsis being routinely used in critical care setting for rapid diagnosis and early initiation of antimicrobial agents. Serial monitoring of procalcitonin also correlates well with the progression of sepsis. Though procalcitonin has a high specificity for bacterial sepsis, there are conditions associated with elevation of procalcitonin in the absence of sepsis which need to be considered when there are no signs of improvement with treatment in a patient suspected to have sepsis. We present a case of acute myeloid leukemia (AML) with elevated procalcitonin in a patient with no evidence of sepsis or autoimmune disorder. After initiation of chemotherapy, the patient’s general condition improved and there was a dramatic fall in procalcitonin level.